Venha ver o congo passar, que coisa mais bela: o turismo cultural em Ituiutaba, Minas Gerais. - Cândido, Tarcísio Luiz (2024)
In the city of Ituiutaba, located in the Triângulo Mineiro region, state of Minas Gerais, we find the subject of analysis for the development of this study: cultural tourism linked to Congado. The main objective of this research was to understand how tourist activity is energized in the city during the celebration of the cultural manifestation belonging to the local Congado community. From a theoretical perspective, the study aligns with a qualitative approach, incorporating elements of participant observation and ethnography. This work is justified as it provides new insights into tourist activity in the city of Ituiutaba. It may also contribute to discussions on municipal public policies that more comprehensively consider the participation of cultural manifestations in their formulations. The methodology was based on a review of bibliographic data for discussing concepts, as well as the documentary analysis of plans, programs, and projects related to tourism at the federal, state, and municipal levels. Fieldwork was also conducted for the collection of empirical data (direct observation, interviews, and photographs), allowing documentation of how local tourism is conceived and structured in the city of Ituiutaba, and how it unfolds during the Congado festivities. Furthermore, it highlighted the various social and hospitable relationships that occur within the cultural community. The research highlights that the city of Ituiutaba has the elements and structure to develop tourism on a larger scale with greater returns. However, it lacks professionals who have the ability to approach tourism from a marketing and social perspective within the public sector. It indicates that the current perception of tourism is superficial and misguided, primarily based on media-driven ideas, neglecting the entire body of Brazilian scientific production on the subject. It also demonstrates that both the Brotherhood of São Benedito and the Municipal Department of Economic Development and Tourism do not make efforts to implement activities during the Congado festivities that go beyond the already established ones. To address these gaps, one of the key players in this scenario, the Municipal Department of Economic Development and Tourism, needs to have a better understanding of the tools at its disposal and use them more efficiently. This involves working with communication that genuinely listens to those directly in contact with visitors, tourists, and the community in general.